Dry deposition of SO2 over Dry Dipterocarp Forest, Thailand - Phuvasa Chanonmuang; Pojanie Khummongkol; Kazuhide Matsuda (Universiti Kebangsaan Malaysia, 2015)
The aerodynamic gradient method was applied to estimate dry deposition flux of SO2 over dry deciduous forest in Nakorn Ratchasima province, Thailand. The meteorological parameters and concentrations of SO2 were measured in real time for one year on the experimental tower at 36 and 27 m high. The flux observed in the wet season were found two times higher than the value observed in the dry seasons, i.e. 20±7.58 and 10±11.05 ng m-2 s-1, respectively. The leaf area index and the ambient humidity were believed to assert the rate of SO2 deposition. The average friction velocities were estimated to be 0.26±0.02 and 0.48±0.06 m s–¹, for the dry and the wet season, respectively. The friction velocity was very much depended on the surface roughness of the forest canopy. The Vd of SO2 evaluated by the aerodynamic gradient was compared with Vd calculated by the resistance model. It was found that the observed Vd was in close proximity with the model prediction in daytime in all conditions, i.e. wet, dry and annual average. The annual average Vd determined by the Aerodynamic gradient was 0.43±0.06 cm s-1.